COMPARATIVE ANALYSIS OF ULTRASOUND AND RADIOGRAPHIC EVALUATION IN DEVELOPMENTAL DYSPLASIA OF THE HIP IN YOUNG CHILDREN - Uraqova Shaxlo Turdiyevna; Raxmatullayev Firdavs Akmalovich; Ravshanov Yahyobek Jahon o‘g‘li; Azamov Zufar Voxidjon o‘g‘li (JOURNAL OF NEW CENTURY INNOVATIONS, 2026)
Abstract: Developmental dysplasia of the hip (DDH) is one of the most common congenital musculoskeletal disorders in infants, with early diagnosis being critical for optimal treatment outcomes. This study provides a comprehensive comparative analysis of ultrasound (US) and radiographic (X-ray) imaging modalities in the evaluation of DDH in children. Ultrasound, primarily using the Graf method, serves as the gold standard for infants under 4-6 months due to its ability to visualize unossified cartilaginous structures and its lack of ionizing radiation [Krauss et al., 2025, p. 2]. Radiography becomes the preferred modality after the appearance of femoral head ossification nuclei, typically between 4-9 months, allowing assessment of acetabular index, Shenton’s line integrity, and femoral head position [Alam et al., 2025, p. 3]. Key findings reveal significant discrepancies between the two modalities: while ultrasonographic hip maturation may appear complete, radiographic assessment can demonstrate persistent pathology in 38% of cases [Atalar et al., 2020, p. 228]. The sensitivity of ultrasound compared to radiography as the reference standard is approximately 45.7%, with specificity of 100% [Atalar et al., 2020, p. 229]. Recent advances include AI-assisted automated analysis achieving Graf angle error rates of 0.21 and three-dimensional ultrasound improving inter-observer reliability [Lee et al., 2025, p. 5; Ghasseminia et al., 2021, p. 1458]. This review emphasizes that ultrasound and radiography are complementary rather than interchangeable, with optimal diagnostic accuracy achieved through age-appropriate modality selection and integrated interpretation of both imaging techniques.